COMPETENCES AND PROFESSIONAL TEACHER COMPETENCES AS THE BASIC TERMINOLOGICAL CONCEPTS - BASLER, Jaromir (Trends in education, 2021)
Scientific literature often uses the term competences. The frequently used concept in the context of education is the derived term professional teacher competences. However, there is a degree of disunity in the use of these concepts. The aim of the present paper is to perform an analysis of professional resources that include these terms, and to clarify the meaning of the terms competences and professional teacher competences in the context of the current educational theory. At first, the paper analyses the term competences and then the derived term professional teacher competences.
Keywords: competences; professional teacher competences; terminology